Effectivity of injection sclerotherapy with sodium tetra decyl sulphate in the management of first and second-degree hemorrhoids - Rohit, Dushyant Kumar; Thakur, Omkar; Verma, R. S.; Pandey, Grishmraj (International Surgery Journal, 2018)
Background: Haemorrhoids are one of the common surgical conditions affecting anorectal region with prevalence of 4% of the population. It is usually defined as increase in size as well as downward disruption of normal functional architecture known as anal cushions. Injection sclerotherapy is time honoured outpatient’s procedure that is widely practised globally to treat first and second-degree haemorrhoids. Methods: This prospective study includes 52 patients who were underwent injection sclerotherapy at Bundelkhand Medical College and Associated Hospital Sagar from August 2015 to September 2016. Patients above the age of 18 years of both sexes with Ist and IInd degree hemorrhoids were included in the study. Pregnant patients, patients with diabetes mellitus and with third and fourth degree hemorrhoids were excluded from the study. A detailed history, clinical presentation, digital rectal examination, proctoscopy and routine investigation were done in all cases. Results: In the present study most of the patients were male. Patients with age group ranging from 20-40 year were found of high incidence of haemorrhoids (86.53%). In present study after three doses of injection 94.23% had satisfactory result. After the first dose injection 71.15% patients had satisfactory results rest 15 patients were given second dose of injection of which 60% patients had satisfactory results. Third dose of injection given to the remaining 06 patients proved satisfactory results in only 03 cases. After three doses of injection 03 cases (5.76%) failed to show any response. Conclusions: Sclerotherapy as a safe, easy, cheap and effective method of treatment of 1st and 2nd degree haemorrhoid devoid of any significant complication.